Analisis Komparasi Kinerja Keuangan Perbankan Syariah di Indonesia dan Malaysia Menggunakan Pendekatan Maqashid Sharia Index - Tiara Tresnawulan Barkah; Dimas Sumitra Danisworo; Muhamad Umar Mai (Journal of Applied Islamic Economics and Finance, 2021)
This research was conducted to analyze the performance of Islamic banking in Indonesia and Malaysia using the Maqashid Sharia Index. The research used Simple Additive Weigting method and independent analysis t-test. From this research it can be concluded that the performance value of Islamic banking in Indonesia using the Maqashid Sharia Index in 2014-2018 is 1.534 and Malaysia is 0.823. Based on the analysis of the independent t test, there is a significant difference between the average value of Islamic banks in Indonesia and Malaysia with a value of Tcount 2.819>Ttable 2.306, MSI's first goal is to obtain T-count value of 1.189 <2.306. The second objective of MSI is to get the T-count value of 2.327> 2.306. The third objective of MSI with T-count value of 1.856 <2.306 T table. This means that there is a significant difference in financial performance with MSI in Indonesia and Malaysia.